Validation of Fast Site-Specific Mean-Value Models for Indoor Propagation - Trueman, C. W.; Davis, D.; Segal, B.; Muneer, W. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A fast assessment of the local mean value of the electric field strength throughout a floor plan is useful for the design of local-area networks. Site-specific models require coding the location of walls, doorways, and other features and modelling their structure and electrical properties. Using ray tracing to find the field strength throughout the floor plan is slow and expensive because a grid of closely-spaced points is needed to trace the rapid variations called fast fading; then the raytracing local area average is found by explicit spatial averaging, to obtain the slow fading behavior. The raytracing mean value is obtained by combining the amplitudes of the fields associated with the rays on an energy basis; widely-spaced grid points can be used because the local mean value varies slowly with position, making the calculation fast and inexpensive. The Sabine method provides a energy-balance approach for an inexpensive estimate of the local mean value field strength. This paper tests the accuracy of the fast methods (the ray-tracing mean value and the Sabine mean value) against the local area average found from dense ray tracing, and against measurements. In a 40 m2 room of roughly square floor plan, the fields from the fast methods were close to those of dense ray tracing and to the measurements. But it is shown that in a long corridor, the ray-tracing mean value and the Sabine mean value were low compared to dense ray tracing, and so these fast methods should be used with caution.